The Guideline for Development Educational Institutions are Learning Organizations in The Network Group to Promote the Efficiency of Special Education Center Network 9: The Guideline for Development Educational Institutions are Learning Organizations in The Network Group to Promote the Efficiency of Special Education Center Network 9 - Phabchanda, Umaporn; Duangchatom, Kritkanok (RATANABUTH JOURNAL, 2023)
The purposes this research were to 1) study the current conditions, desirable condition and need assessment of development educational institutions are learning organizations in the network group to promote the efficiency of special education center network 9. 2) study and evaluation the guideline for development educational institutions are learning organizations in the network group to promote the efficiency of special education center network 9. The research was divided into 2 phases: Phase 1 study the current conditions, desirable condition and need assessment of development educational institutions are learning organizations. The sample group were 291 school administrators and teachers. The research instrument were questionnaires. The statistics used for data analysis were mean and deviation standard. Phase 2: study and evaluation the guideline for development educational institutions are learning organizations. The target groups include 9 experts for assess suitability possibility of guideline. The research instrument were interview form and assessment form of guidelines The results of the research were as follows: The current state in overall was moderate level, the desirable state in overall was in the highest level. The need assessment rank from high to low level was 1) System thinking 2) Personal mastery 3) Team learning 4) Mental model 5) Shared vision 2. the guideline for development educational institutions are learning organizations the guideline for development educational institutions are learning organizations was development program, Include was 1 principles, 2) objectives, 3) contents, 4) development activities, and 5) measurement and evaluation. The Content consists of 5 module Include, module 1 system thinking, module 2 personal mastery, module 3 team learning, module 4 mental model, module 5 Shared vision. Summary of guidelines evaluation, feasibility and utility was the highest in overall.